2016
DOI: 10.1002/adma.201602869
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Engineering of Hierarchically Porous NiTi/Hydrogels Nanocomposites with Exceptional Antibiofouling Surfaces

Abstract: Seamlessly bridging the hard and the soft, a strategy to fabricate hierarchically porous NiTi/hydrogels nanocomposites is reported. The nanocomposite surface can hold high-content water while keeping its hierarchical nanoscale topography, thus showing exceptional antibiofouling performance. This strategy will lead to antibiofouling alloy (e.g., NiTi)/hydrogel nanocomposites for improved stents and other blood-contacting implants and medical devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 42 publications
1
36
0
2
Order By: Relevance
“…Zhang et al fabricated fibrillar anionic and zwitterionic hydrogel brushes using anodic aluminum oxide (AAO) as a template to improve the antibiofouling property. [117] In comparison to pristine NiTi, porous NiTi/hydrogel nanocomposites have the same level of mechanical durability and integrity after 100 cycles of bending and twisting tests. These fibrillar hydrogel surfaces exhibited underwater superoleophobicity and extremely low oil adhesion.…”
Section: Antibiofoulingmentioning
confidence: 95%
See 1 more Smart Citation
“…Zhang et al fabricated fibrillar anionic and zwitterionic hydrogel brushes using anodic aluminum oxide (AAO) as a template to improve the antibiofouling property. [117] In comparison to pristine NiTi, porous NiTi/hydrogel nanocomposites have the same level of mechanical durability and integrity after 100 cycles of bending and twisting tests. These fibrillar hydrogel surfaces exhibited underwater superoleophobicity and extremely low oil adhesion.…”
Section: Antibiofoulingmentioning
confidence: 95%
“…Similarly, by infusing silicone oil into PDMS with vascular networks, Howell et al reported an organogel-based Adv. [117] Copyright 2017, John Wiley & Sons, Inc. e) Illustration of slippery organogel surfaces for easy-sliding of water droplets. 2019, 6, 1900996 Figure 9.…”
Section: Antibiofoulingmentioning
confidence: 99%
“…Additionally, this study also offers a novel design concept for preparation of liquid‐repellent surfaces by introducing another immiscible liquid layer into solid surface structures, which is adopted for fabrication of slippery liquid‐infused porous surfaces . Inspired by the underwater superoleophobic property of fish scales, artificial hydrogel surfaces that can absorb a large amount of water exhibit underwater superoleophobicity and underoil superhydrophilicity. Similarly, organogel surfaces that can absorb oil exhibit underwater superoleophilicity and underoil superhydrophobicity.…”
Section: Bioinspired Superwettability Systems Based On Binary Cooperamentioning
confidence: 99%
“…Hydrogel has been actively investigated as antifouling coating material due to its soft, high-water-content, reducing effective attached area, and low surface energy just like fish slime [9] However, developing absolute hydrogel coatings seems extremely difficult, if not totally impossible, due to its poor adhesion strength to substrates. In this paper, the coating modified by PVA/PAAm hydrogel powder was prepared.…”
Section: Introductionmentioning
confidence: 99%